2017
DOI: 10.1111/nyas.13335
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on evidence‐based adolescent nutrition interventions

Abstract: Adolescence is a critical stage in the life cycle, and adequate nutrition is necessary for the proper growth and development of individuals and their offspring. Here, we comprehensively review all published systematic reviews (through October 2016) on adolescents (10-19 years) and women of reproductive age, including pregnant women, which targeted interventions related to nutrition. For interventions where there was no existing systematic review on adolescents, we reviewed primary studies/trials. We included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 132 publications
(316 reference statements)
2
111
0
3
Order By: Relevance
“…The multiple micronutrient intervention had modest significant benefits and may be a better way to combine provision of individual nutrients. In addition, randomized trials of iron supplementation have been shown to significantly improve hemoglobin concentrations among adolescents (standardized mean difference 1.83, 95% CI 0.59–3.08) based on pooled analysis of 7 studies [43]. Despite the lack of impact on linear growth, this intervention may be worth considering, given the benefit of iron supplementation on cognition in school age children [44].…”
Section: Adolescent Growth and Developmentmentioning
confidence: 99%
“…The multiple micronutrient intervention had modest significant benefits and may be a better way to combine provision of individual nutrients. In addition, randomized trials of iron supplementation have been shown to significantly improve hemoglobin concentrations among adolescents (standardized mean difference 1.83, 95% CI 0.59–3.08) based on pooled analysis of 7 studies [43]. Despite the lack of impact on linear growth, this intervention may be worth considering, given the benefit of iron supplementation on cognition in school age children [44].…”
Section: Adolescent Growth and Developmentmentioning
confidence: 99%
“…In summary, the general evidence indicates that the means for reducing the risk of stillbirths, neonatal mortality, and LBW are the same for pregnant women across all age groups, including adolescents. Iron supplementation significantly improves hemoglobin concentration and potentially reduces anemia; periconceptional folic acid supplementation can reduce neural tube defects; and high‐dose (≥1 g daily) calcium intake among pregnant women at risk of low calcium intake reduces the risk of preeclampsia, preterm birth, and neonatal high‐care admissions .…”
Section: Evidence‐based Nutrition Recommendations For Adolescentsmentioning
confidence: 99%
“…Iron supplementation significantly improves hemoglobin concentration and potentially reduces anemia; periconceptional folic acid supplementation can reduce neural tube defects; and high‐dose (≥1 g daily) calcium intake among pregnant women at risk of low calcium intake reduces the risk of preeclampsia, preterm birth, and neonatal high‐care admissions . Specific studies among adolescent women indicate that zinc supplementation among adolescents is associated with improvements in serum zinc and in hemoglobin concentration, and supplementation among pregnant adolescents significantly reduced preterm birth rates and LBW …”
Section: Evidence‐based Nutrition Recommendations For Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations